2020
DOI: 10.1093/nar/gkaa1117
|View full text |Cite
|
Sign up to set email alerts
|

MiR-CLIP reveals iso-miR selective regulation in the miR-124 targetome

Abstract: Many microRNAs regulate gene expression via atypical mechanisms, which are difficult to discern using native cross-linking methods. To ascertain the scope of non-canonical miRNA targeting, methods are needed that identify all targets of a given miRNA. We designed a new class of miR-CLIP probe, whereby psoralen is conjugated to the 3p arm of a pre-microRNA to capture targetomes of miR-124 and miR-132 in HEK293T cells. Processing of pre-miR-124 yields miR-124 and a 5′-extended isoform, iso-miR-124. Using miR-CLI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 56 publications
(85 reference statements)
0
17
0
Order By: Relevance
“…Therefore, the improvement of new strategies to discriminate selective targets for these novel microRNA variants is primary. In this context, the miR-CLIP technique ( Imig et al, 2015 ), based on the transfection of pre-miRNAs conjugated with biotin and psoralen to trap mRNA targets in cells, aided the identification of targets differentially regulated by miR-124 and its 5′ isoform ( Wang et al, 2020 ). After the transfection of a modified pre-miRNA-124 miR-CLIP probe in HEK293T cells, supported by the subsequent individual transfection of canonical and isomiR-124, the authors identified 16 potential targets ( Wang et al, 2020 ).…”
Section: The Functional Importance Of Isomirsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the improvement of new strategies to discriminate selective targets for these novel microRNA variants is primary. In this context, the miR-CLIP technique ( Imig et al, 2015 ), based on the transfection of pre-miRNAs conjugated with biotin and psoralen to trap mRNA targets in cells, aided the identification of targets differentially regulated by miR-124 and its 5′ isoform ( Wang et al, 2020 ). After the transfection of a modified pre-miRNA-124 miR-CLIP probe in HEK293T cells, supported by the subsequent individual transfection of canonical and isomiR-124, the authors identified 16 potential targets ( Wang et al, 2020 ).…”
Section: The Functional Importance Of Isomirsmentioning
confidence: 99%
“…In this context, the miR-CLIP technique ( Imig et al, 2015 ), based on the transfection of pre-miRNAs conjugated with biotin and psoralen to trap mRNA targets in cells, aided the identification of targets differentially regulated by miR-124 and its 5′ isoform ( Wang et al, 2020 ). After the transfection of a modified pre-miRNA-124 miR-CLIP probe in HEK293T cells, supported by the subsequent individual transfection of canonical and isomiR-124, the authors identified 16 potential targets ( Wang et al, 2020 ). Out of these 16 selected candidates, 12 were mostly regulated by canonical miR-124, three were regulated by both isoforms, and just one was strongly inhibited exclusively by isomiR-124 ( Wang et al, 2020 ).…”
Section: The Functional Importance Of Isomirsmentioning
confidence: 99%
See 1 more Smart Citation
“…An example of how isomiRs can promote noncanonical gene targeting is provided by miR-124. The processing of pri-miR-124 generates two 5′ isomiRs, derived from seed sequences shifted by a single nucleotide, which act by regulating different transcripts, contained in overlapping targetomes [169]. Next-generation sequencing data obtained from hESCs (CyT49 (Via-Cyte), H1, and H9 cell lines) led to the identification of some miRNAs, such as miR-302, whose stem loop generates different highly expressed isomiRs, with important roles in hESC self-renewal [170].…”
Section: Noncanonical Gene Targeting Of Micrornasmentioning
confidence: 99%
“…MiRNA‐mRNA products are isolated on streptavidin beads, and targets are identified by RNA sequencing. A strength of miR‐CLIP is that non‐canonical targets, i. e. new functions of miRNAs that are difficult to identify by other means, can be identified [8c,14] …”
Section: Introductionmentioning
confidence: 99%